Face memory and face recognition in children and adolescents with attention deficit hyperactivity disorder: A systematic review. (June 2018) - Romani, Maria; Vigliante, Miriam; Faedda, Noemi; Rossetti, Serena; Pezzuti, Lina; Guidetti, Vincenzo; Cardona, Francesco
Highlights: A systematic review focused on facial recognition in ADHD children and adolescents is proposed. The literature on this argument focused mainly on hot aspects (e.g. emotion recognition, theory of mind) of face recognition. The literature on this argument taking no account of neuropsychological and cognitive elaboration of faces in ADHD children. Previous studies showed a wide and heterogeneous use of tasks to assess emotion recognition and facial expressions. The abilities of memory and recall for faces in ADHD children and adolescents, did not receive much attention in literature. Abstract: This review focuses on facial recognition abilities in children and adolescents with attention deficit hyperactivity disorder (ADHD). A systematic review, using PRISMA guidelines, was conducted to identify original articles published prior to May 2017 pertaining to memory, face recognition, affect recognition, facial expression recognition and recall of faces in children and adolescents with ADHD. The qualitative synthesis based on different studies shows a particular focus of the research on facial affect recognition without paying similar attention to the structural encoding of facial recognition. In this review, we further investigate facial recognition abilities in children and adolescents with ADHD, providing synthesis of the results observed in the literature, while detecting face recognition tasks used on face processing abilities in ADHD and identifying aspects not yet explored.